Implementation of Google Classroom, YouTube, and Quizizz Multimedia to Improve Students’ Motivation and Cognitive Learning Outcomes in Islamic Religious Education Learning - R. Muhamad Yasin Fadilah; Aan Hasanah; Mohamad Erihadiana; Nurhamzah Nurhamzah (International Journal of Islamic Educational Research, 2026)
This study was motivated by the low levels of student motivation and cognitive learning outcomes in the Islamic Education (PAI) subject at SMK Pasundan 1 and SMK Bunga Persada Cianjur. The phenomenon was identified through preliminary observations showing that 45% of students scored below the Minimum Mastery Criteria (KKM) and demonstrated low engagement during the learning process. The school’s efforts to improve student motivation and learning outcomes have not been optimal, as teaching methods and media are still largely limited to conventional approaches. Therefore, innovation in learning through the use of technology-based interactive multimedia such as Google Classroom, YouTube, and Quizizz is needed to create more engaging and effective learning experiences. The objectives of this study were to identify: (1) the implementation of Google Classroom, YouTube, and Quizizz multimedia in PAI learning; (2) students’ learning motivation; (3) students’ cognitive learning outcomes; (4) the influence of multimedia implementation on students’ learning motivation; (5) the influence of multimedia implementation on students’ cognitive learning outcomes; and (6-8) the qualitative findings that expand and deepen the quantitative results regarding multimedia implementation, learning motivation, and cognitive learning outcomes at SMK Pasundan 1 and SMK Bunga Persada Cianjur. This research employed a Mixed Methods approach using a sequential explanatory design, combining quantitative and qualitative methods in sequence. Data were collected through questionnaires, interviews, observations, and document analysis.